Analysis of Nutritional Status, Reproductive Health Risk, and Psychological Distress among Senior High School Adolescents: A School-Based Cross-Sectional Study - Roichatul Djannah; Sigit Nurcahyono (Lembaga Publikasi Ilmiah Nusantara, 2026)
Adolescence is a critical developmental period characterized by rapid biological, psychological, and social changes that may increase vulnerability to reproductive health problems and psychological distress. This study examined the relationships among nutritional status, reproductive health risks, and psychological distress among adolescents. A quantitative cross-sectional study was conducted among 198 senior high school students. Nutritional status was assessed using BMI-for-age anthropometric measurements, while reproductive health risk and psychological distress were measured using structured questionnaires, including the Kessler Psychological Distress Scale-10 (K10). Data were analyzed using univariate analysis, the Chi-Square test, Spearman's rank correlation, and linear regression. Most respondents had normal nutritional status (65.7%), moderate reproductive health risk (87.4%), and severe psychological distress (77.3%). Nutritional status was not significantly associated with reproductive health risk (p = 0.9288) or psychological distress (p = 0.7764). In contrast, reproductive health risk showed a significant association with psychological distress (p < 0.001; ρ = 0.3939). Multivariate analysis confirmed reproductive health risk as a significant predictor of psychological distress (β = 0.829; p < 0.001), explaining 15.4% of the variance. These findings highlight the importance of integrating reproductive health screening, counseling, and mental health support into school-based adolescent health programs.